Protective and Detrimental Roles of p38α Mitogen‐Activated Protein Kinase in Different Stages of Nonalcoholic Fatty Liver Disease. Issue 3 (28th September 2020) - Hwang, Seonghwan; Wang, Xiaolin; Rodrigues, Robim M.; Ma, Jing; He, Yong; Seo, Wonhyo; Park, Seol Hee; Kim, Seung‐Jin; Feng, Dechun; Gao, Bin
Abstract : Background and Aims: Neutrophil infiltration is a hallmark of nonalcoholic steatohepatitis (NASH), but how this occurs during the progression from steatosis to NASH remains obscure. Human NASH features hepatic neutrophil infiltration and up‐regulation of major neutrophil‐recruiting chemokines (e.g., chemokine [C‐X‐C motif] ligand 1 [CXCL1] and interleukin [IL]‐8). However, mice fed a high‐fat diet (HFD) only develop fatty liver without significant neutrophil infiltration or elevation of chemokines. The aim of this study was to determine why mice are resistant to NASH development and the involvement of p38 mitogen‐activated protein kinase (p38) activated by neutrophil‐derived oxidative stress in the pathogenesis of NASH. Approach and Results: Inflamed human hepatocytes attracted neutrophils more effectively than inflamed mouse hepatocytes because of the greater induction of CXCL1 and IL‐8 in human hepatocytes. Hepatic overexpression of Cxcl1 and/or IL‐8 promoted steatosis‐to‐NASH progression in HFD‐fed mice by inducing liver inflammation, injury, and p38 activation. Pharmacological inhibition of p38α/β or hepatocyte‐specific deletion of p38a (a predominant form in the liver) attenuated liver injury and fibrosis in the HFD +Cxcl1 ‐induced NASH model that is associated with strong hepatic p38α activation. In contrast, hepatocyte‐specific deletion of p38a in HFD‐induced fatty liver where p38α activation is relatively weak exacerbated steatosis and liver injury. Mechanistically, weak p38α activation in fatty liver up‐regulated the genes involved in fatty acid β‐oxidation through peroxisome proliferator‐activated receptor alpha phosphorylation, thereby reducing steatosis. Conversely, strong p38α activation in NASH promoted caspase‐3 cleavage, CCAAT‐enhancer‐binding proteins homologous protein expression, and B cell lymphoma 2 phosphorylation, thereby exacerbating hepatocyte death. Conclusions: Genetic ablation of hepatic p38a increases simple steatosis but ameliorates oxidative stress‐driven NASH, indicating that p38α plays distinct roles depending on the disease stages, which may set the stage for investigating p38α as a therapeutic target for the treatment of NASH.